Avaliação de desempenho funcional no âmbito do MPC/PA: um diagnóstico a partir da percepção dos servidores da instituição - COSTA, Bruna Aline Bentes da (Universidade Federal do Pará, 2024)
The present dissertation addresses the evaluation of functional performance within the Public Accounts Office of Pará (MPC/PA), an institution that implemented this process in 2018 and has not conducted any diagnostic since then. Furthermore, although this topic is more common in the private sector, it has gained prominence in the public service. Therefore, given the importance of the subject, the research was guided by the following question: In the perception of MPC/PA employees, what does the diagnosis of functional performance evaluation reveal for the improvement of the process? The general objective was to assess the perception of MPC/PA employees regarding the current functional performance evaluation process in order to enhance the evaluation instrument. In this direction, the specific objectives outlined for the study were: a) Identify the limits and challenges of the functional performance evaluation system carried out by MPC/PA, and b) Identify actions that can be adopted by MPC/PA to improve the employee performance evaluation process. The theoretical approach used encompasses the conception of performance evaluation throughout the evolution of personnel management, its limits, challenges, and its relationship with public administration, as well as the various reforms carried out in the public administration during this period. The research methodology included bibliographic research, documentary analysis, and a case study conducted through a questionnaire. This questionnaire, in addition to collecting participant profiles, included six dimensions related to the performance evaluation process: general aspects, culture, leadership, compensation, team, and fairness. The research instrument was directed to all MPC/PA employees and had 68 respondents out of a population of 77 individuals. Among the main results, employees' perception revealed a desire for the performance evaluation process to be reformulated and improved, its contribution to functional enhancement, the leadership of supervisors, the benefits and challenges of linking compensation to performance evaluation results, organizational immaturity in relation to performance evaluation, and employees' desire to evaluate their immediate supervisors. Based on this, it was possible to identify the limits and challenges of the MPC/PA's performance evaluation system and propose actions for process improvement.